2012
DOI: 10.1590/s0034-71672012000200016
|View full text |Cite
|
Sign up to set email alerts
|

Mensuração de área de úlceras por pressão por meio dos softwares Motic e do AutoCAD®

Abstract: Pressure ulcer is a lesion that affects skin layers in some regions of the body and its healing can be followed up using image processing. The analysis of pressure ulcer area is relevant to evaluate its evolution and response to therapeutic procedures. Such areas can be evaluated through contour marking with the softwares Motic and AutoCAD®. In this study 35 volunteers computed areas from two grade III pressure ulcers using these instruments. It was possible to conclude that results are clinically equivalent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
1
2
0
6
Order By: Relevance
“…Another study 5 that compared the AutoCAD (r) software with another program also found that marking offsets, the relative point of view, is larger in wounds with a smaller area, since it requires hand movements of the operator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study 5 that compared the AutoCAD (r) software with another program also found that marking offsets, the relative point of view, is larger in wounds with a smaller area, since it requires hand movements of the operator.…”
Section: Discussionmentioning
confidence: 99%
“…Among the software available for measurement, two programs can be used: AutoCAD (r) software and the Image Tool. The first is a program commonly used by engineers in topography for physical area calculation 5 and the second was developed by the University of Texas Health Sciences Center at San Antonio, and is a free software used as a tool to obtain objective and reliable measures to the real size of the lesion 6 .…”
Section: Introductionmentioning
confidence: 99%
“…O estudo que comparou o software AutoCAD ® com o Motic concluiu que ambos apresentam pequenos erros de medida. Houve diferença estatística e encontrou-se baixa reprodutibilidade, entretanto, os programas concordam entre si e são mais confiáveis do que as técnicas simples de mensuração de área, permitindo melhor acompanhamento da evolução de feridas 13 .…”
Section: Técnicas Não Invasivas Para Mensuração De Feridasunclassified
“…O software Image Tool, desenvolvido pela University of Texas Health Sciences Center at San Antonio, é apresentado como um instrumento prático, capaz de obter medidas objetivas, fidedignas ao tamanho real da lesão, conferindo segurança, rapidez e confiabilidade ao processo de mensuração (3) . Em revisão da literatura realizada para este projeto, encontrou-se um estudo que comparou o programa AutoCAD® com outro software (2) , entretanto não foram descobertas pesquisas que avaliaram o outro programa citado, nem que compararam os dois programas.…”
Section: Situação Problema E Sua Significânciaunclassified